TIKTOK SEBAGAI MEDIA TEKNOLOGI DIGITAL DALAM PENYAJIAN KONTEN DAKWAH BAGI GENERASI Z DI KALANGAN MAHASISWA UPI PURWAKARTA - Annisa Salsabila; Joya Nuraini; Nabilah Rangkuti; Nurani Laraswati; Rika Aprilia; Hisny Fajrussalam; Yahya Rafi Sya'bani (Bayan lin-Naas : Jurnal Dakwah Islam, 2026)
The rapid development of digital technology has transformed the way religious values are disseminated, including through social media platforms such as TikTok. However, the presentation of short, fast, and algorithm-based da’wah content also raises concerns regarding shallow religious understanding, filter bubble effects, the dominance of viral-oriented content, and the low level of digital literacy among students. This study aims to analyse TikTok as a digital technology medium in presenting da’wah content for Generation Z among students at Universitas Pendidikan Indonesia (UPI) Purwakarta Campus. The study employed a survey method with a quantitative approach. Data were collected through Google Form questionnaires distributed to 52 students from various study programs at UPI Purwakarta Campus. The research instrument used a Likert scale to measure the intensity of TikTok usage, exposure to da’wah content, content-viewing behaviour, the effectiveness of TikTok as a digital medium, and perceptions regarding the impact of digital da’wah content. The findings show that 96.2% of respondents were active TikTok users, while 86.5% used TikTok for a considerable duration each day. In addition, 65.4% of respondents frequently encountered da’wah content on their For You Page (FYP), whereas 57.68% tended to watch da’wah content until the end when it was considered interesting and relevant. Furthermore, 73.1% of respondents viewed TikTok as a practical medium for obtaining religious information, and 80.8% considered da’wah content on TikTok beneficial to their religious understanding. These findings indicate that TikTok plays a significant role as a digital technology medium in presenting da’wah content for Generation Z due to its ability to disseminate information quickly, visually, interactively, and accessibly. Nevertheless, strengthening digital literacy remains important so that religious information received through TikTok can be understood critically and responsibly.